Nutritional Diversity in Native Germplasm of Maize Collected From Three Different Fragile Ecosystems of India - Langyan, Sapna; Bhardwaj, Rakesh; Kumari, Jyoti; Jacob, Sherry Rachel; Bisht, Ishwari Singh; Pandravada, Someswara Rao; Singh, Archna; Singh, Pratap Bhan; Dar, Zahoor Ahmed; Kumar, Ashok; Rana, Jai Chand (Frontiers in Nutrition, 2022)
Native germplasm resources are adapted to specific ecological niches and have sustained over generations owing to preference of local communities for their unique taste, utility for specific dishes and low cost of cultivation. They may help in eradicating malnutrition and act as source for trait linked genes. The present dataset comprises of thirty three native germplasm of maize collected from Rajasthan, Himachal Pradesh and Andhra Pradesh states of India with an altitudinal variation of 386–2028 (m), which were evaluated for proximate composition, minerals, nutritional attributes and antioxidant activity and compared with the standard values reported in Indian Food Composition Table (IFCT), 2017.The nutritional profile of these germplasm showed moisture content in the range of 7.16 to 12.37%, ash from 0.73 to 1.93%, crude protein from 8.68to 12.01%, crude fat from 3.72 to 8.03%, crude fiber from 5.21to 11.23% and available carbohydrates by difference of 60.59 to 69.77%. Three accessions namely, Malan -11(7.06%), Malan -24 (7.20%) and Yellow Chamba Local-02 (8.03%) exhibited almost a double the crude fat content as compared to the values notified in IFCT (3.77).Total sugar content obtained was in the range of 5.00 to 11.30% whereas the starch content was found between 50.89 to 64.93%.All the germplasm except Yellow Chamba Local reflected higher amount of protein as compared to reported values in IFCT (8.80). Accessions in Sathi, Safed Chamba Local and Ragal Makka had nearly 12% protein content. Mineral malnutrition, particularly due to iron (Fe) deficiency, is a world-wide issue to science, humanity and society. Mineral profile revealed that most of the germplasm had higher content of Iron. Accessions with iron content of nearly three times of IFCT reported value were identified in germplasm belonging to three states. Negative relationship was observed between altitude of sample collection site and available carbohydrate content, whereas available carbohydrate had negative relationship with dietary fiber, protein and fat content. Information generated in this study can be utilized for promoting these germplasm as nutrifood, nutritional surveillance, labeling and in crop improvement programmes.